Resilience and Protection of Critical Information Infrastructure Resilience and Protection of Critical Information Infrastructure - Hruza, Petr (Communications - Scientific letters of the University of Zilina, 2018)
The article deals with resilience and protection of critical information infrastructure elements. The elements affect rapid recovery of the system to its original state and the increase of resistance during the subsequent emergency events. The article also deals with sectoral and cross-sectional criteria for determining the critical information infrastructure elements, which are closely related to resilience and protection. Risk assessment has been conducted in the area of critical information infrastructure. Finally, amendments of the Czech Cyber Security Act have been mentioned.